Effect of supplementation with different sources and levels of zinc, copper, and manganese on the reproductive development of laying hens - Joelma Vasconcelos Celestino da Silva; Adiel Vieira de Lima; Anna Neusa Eduarda Ferreira de Brito; Thamires da Silva Ferreira; Isabelle Naemi Kaneko; Leonardo Augusto Fonseca Pascoal; Matheus Ramalho de Lima; Ricardo Romão Guerra; Apolônio Gomes Ribeiro; Jorge Cunha Lima Muniz; Lucas Rannier Ribeiro Antonino Carvalho; Fernando Guilherme Perazzo Costa (Poultry Science)
The study evaluated the effects of zinc (Zn), copper (Cu), and manganese (Mn) supplementation from different sources and levels on the performance and reproductive development of Hy-Line W-80 laying hens. A total of 364 birds were assigned to a completely randomized 2 × 2 factorial design, with two mineral sources (sulfate vs. mineral hydroxy‑analogue of methionine) and two supplementation levels (recommended vs. higher than recommended), totaling four treatments with seven replicates. Birds were fed the experimental diets from hatch to 54 weeks of age (378 days). Performance parameters included body weight, feed intake, feed conversion, age at first egg, first egg weight, and egg production from 17 to 54 weeks. Morphological aspects of the magnum and uterus (height, width, and number of folds) were assessed at pre-laying, pre-peak, and laying phases by slaughtering one bird per replicate at 17, 23, and 54 weeks. The first egg was laid at 119 days (34.79 g) in birds receiving sulfate with recommended mineral levels (FS + NR). The shortest interval between first eggs occurred in birds supplemented with the hydroxy‑analogue at higher levels (FQ + NS), which also resulted in improved egg number, weight, and production from 20 to 54 weeks. FS + NR led to better microscopic development of the magnum and uterus at 54 weeks. Overall, Zn, Cu, and Mn supplementation from hatch using the sulfate source at recommended levels benefited initial performance and reproductive development of laying hens until 54 weeks of age.